NanoElectrochemical studies of 2D Materials for Energy Storage and Conversion using Scanning Electrochemical Cell Microscopy - Brunet Cabré, Marc (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2023)
Electrochemical systems are of critical importance in modern society as they enable the conversion of electricity from renewable sources into chemicals and materials. The integration of nanomaterials in energy storage and conversion technologies has resulted in significant advancements, providing improved efficiency and performance to existing technologies while enabling the development of new, cutting-edge technologies. Electrochemical technologies that incorporate nanomaterials are expected to be widespread across industries and society in the years ahead, and therefore understanding the electrochemical behaviour of nanomaterials is crucial. However, it remains a challenge to decipher nanomaterial contributions in electrochemical systems. Recently, new electrochemical methods have emerged that allow for unambiguous characterisation of nanomaterials, the key to which is the isolation of single nanoscale objects or domains. Scanning Electrochemical Cell Microscopy (SECCM) is an advanced nano electrochemical technique for single nano entity electrochemistry. This thesis aims to use SECCM to study the fundamental behaviour of two dimensional nanomaterials (2D materials) relevant for energy storage and conversion, as well as to contribute to the development of new methods for nano electrochemical characterisation. The opening section of this thesis examines the state of the art literature and details the role of nanomaterials in electrochemical systems for energy generation and storage. The introduction section includes examples of state-of-the-art nanomaterials and electrochemical designs. In particular, 2D materials have garnered attention for energy storage and conversion applications because of their attractive properties, such as a large specific surface area and the presence of electrocatalytic sites. One of the most appealing 2D materials are 2D transition-metal dichalcogenides (2D TMDCs), although several questions regarding 2D TMDCs electrochemical behaviour remain open. Previous literature attempted to identify how the morphology of 2D TMDCs affects their electrochemical behaviour, but faced limitations over the resolution of the methods implemented. In this thesis, SECCM is employed to study the electrochemical behaviour of 2D TDMCs and its correlation with nanomaterial morphology, revealing correlations between the number of stacked layers, changes in the band gap, and electrochemical behaviour. Moreover, the great resolution offered by SECCM allowed the detection and characterisation of nanoscale defects on 2D TMDCs, among providing further insights about the role and contribution of nanoscale electrochemical behaviour into the classical macroscale responses. Another 2D material of interest for supercapacitor applications, two-dimensional transition-metal carbides and nitrides (MXenes), are investigated. MXenes exhibit a unique combination of properties: rich surface chemistry and outstanding conductivity. Despite the presence of numerous experimental and computational studies in the literature on MXenes, the response of individual MXene flakes toward psedocapacitive charging has not been thoroughly evaluated. In this thesis, SECCM is used to isolate the response of individual MXene flakes, bridging the gap between previous experimental reports based on macroscale electrodes and computational methods that simulate nanoscale domains. The study uncovers a delocalised surface charging mechanism on MXenes previously unreported. The findings of this thesis contribute to a comprehensive understanding of nanomaterials' electrochemical properties, opening avenues for the development of advanced energy technologies. This thesis also contributes to the field of nano-electrochemistry by introducing new methods and instrumentation. It is presented a custom-made low-noise high bandwidth transimpedance amplifier designed for SECCM, enabling successful single-entity electrochemical characterisation at an unprecedented high bandwidth of 1 MHz.
APPROVED
Keywords: Electrochemistry; 2D Materials; Nanomaterials; SECCM; Energy Storage; Energy Conversion; MXenes; TMDC